Accumulating evidence from meta-analyses of prognostic studies on oral cancer: towards biomarker-driven patient selection - Almangush, Alhadi; Alabi, Rasheed Omobolaji; Pirinen, Matti; Mäkitie, Antti; Leivo, Ilmo (BMC, 2025)
Background
Many histopathologic prognostic markers, identified by routine hematoxylin and eosin (HE) staining, have been proposed for predicting the survival of patients with oral squamous cell carcinoma (OSCC). Subsequently, several meta-analyses have been conducted on these prognostic markers. We sought to analyze the accumulated evidence from these meta-analyses.
Methods
An electronic database search of PubMed, Scopus, Ovid Medline, Web of Science, and Cochrane Library was conducted to retrieve all meta-analysis articles published on histopathologic prognostic markers of OSCC. The risk of bias of the included studies was analyzed using the Risk of Bias in Systematic Reviews (ROBIS) tool. The synthesis of the results was conducted following the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA).
Results
There were 16 meta-analysis articles published on the histological prognostic markers of OSSC. The accumulated evidence from these meta-analyses highlighted the powerful prognostic value of depth of invasion, tumor thickness, perineural invasion, lymphovascular invasion, worst pattern of invasion, tumor budding, and tumor-stroma ratio. The highest odds ratio (OR) of a relationship between a histopathologic prognostic marker and outcome was for the depth of invasion (OR 10.16, 95% CI 5.05-20.46) and tumor thickness (OR 7.32, 95% CI 5.3-10.1) in predicting lymph node metastasis.
Conclusion
The published meta-analyses present robust evidence on the significance of emerging histopathologic markers, namely, worst pattern of invasion, tumor budding, and tumor-stroma ratio. It is time to consider such markers in daily pathology reporting and risk stratification of OSCC.